ANALISA FAKTOR - FAKTOR KEUANGAN TERHADAP RESIKO SISTEMATIS DI BURSA EFEK JAKARTA - Rina Dwiarti (Jurnal Ekonomi dan Bisnis, 2009)
This research has two objectives. The first objective is to analyze the impact of seven fundamentalfactors (Dividend Payout, asset growth, leverage, liquidity, asset size, earnings variability,accounting beta) to the bussiness risk. Bussiness risk are measured by using SingleIndex Model (Beta) and four lag and four lead Fowler and Rorke Method (Corrected Beta).The sample was taken by using purposive sampling method. the taken sample consist of 37companies. The research period devide in two sub period : before crisis Period (1992 up to1996) and after crisis period (1997 up to 2001). The research result show that from the sevenfactors assumed to influence on beta, there are four factors which partially show positive influencein before crisis period : Dividend Payout, liquidity, asset size, earnings variability, andthere are six factors : Dividend Payout, asset growth, leverage, liquidity, asset size, accountingbeta in after crisis period. The other result show that from seven factors assumed to influenceon the corrected beta, there are five factors which partially show positive influence inbefore crisis period : Dividend Payout, asset growth, liquidity, asset size, earnings variabilityon before crisis period, and Five factors too: Dividend Payout, leverage, liquidity, asset size,accounting beta in after crisis period. The result on the Chow test indicated that the effect offundamental factor on bussiness risk are significantly different between before crisis periodand after crisis period.Keywords : Dividend Payout, Asset Growth, Leverage, Liquidity, Single Index Model